PENGARUH KOMPETENSI, STRES KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus Pada PT JNE Cabang Bogor) - Nur Amalia Putri (2022)
This research is a quantitative research that aims to determine and prove the effect of competence, work stress, and work discipline on employee performance. This study used 76 employees of PT JNE Bogor Branch as a sample. The analysis technique used in this study is descriptive analysis technique and inferential analysis using the SmartPLS 4.0 test tool. Testing the hypothesis in this study using the T test with a significance level of 5% (0.05). The results of this study state that (1) competence has a positive and significant effect on employee performance; (2) Work stress has a positive and significant effect on employee performance; (3) Work Discipline has a positive and significant effect on employee performance; and (4) Competence, work stress, and discipline simultaneously affect employee performance.